The Implementation of SAVI (Somatic, Auditory, Visual, and Intellectual) Learning Model toward Critical Thinking Ability of Students in Grade XI on the Subjects of Solubility and Solubility Product Constant (Ksp) - Sarmilah Sarmilah; Afadil Afadil; Vanny M. A. Tiwow (Jurnal Akademika Kimia, 2021)
This study aimed to determine students' critical thinking ability through the implementation of SAVI (somatic, auditory, visual, and intellectual) learning model on the subject of solubility and solubility product constant (Ksp) at SMA Negeri 5 Model Palu. The study used one group pretest-posttest design. The instruments were lesson plans, critical thinking tests, students' worksheets, and validated observation sheets. Data of critical thinking abilities were analyzed using rubrics with three indicators, i.e. interpretation, analysis, and inference. Results of data analysis on students' critical thinking skills at the pretest on each indicators in Experiment class I were 25.84, 11.13, and 2.44%, respectively; while in class II were 23.51, 1.38, and 0%, respectively. The posttest in Experiment class I were 69.94, 61.13, and 53.51%, respectively, while in class II were 79.55, 48.61, and 49.07%, respectively. The average of students' critical thinking skills ability in experiment class I was 61.02%, and class II was 61.47%. Both of them were in the moderate category. This study concludes that students' critical thinking skills ability with the implementation of SAVI learning model is in a good category. The average of students' critical thinking skills ability in experiment class I was 61.02%, and in experiment class II is 61.47%. Both of them were in the moderate critical thinking category. This study concludes that students' critical thinking skills ability with the implementation of SAVI learning model is in a good category.